Frege e as Leis da Aritmética: do ideal de fundamentação ao paradoxo - Coury, Aline Germano Fonseca (2015)
Since the end of the nineteenth century and early twentieth century, some scholars such as Frege, Russell, Dedekind, Wittgenstein, among others, started to seek the foundations of the mathematics. Specifically, Frege developed studies in order to build the arithmetic foundation based on classical logic, i. e., using logic, he intended to build a system capable of formalizing mathematical definitions and proof methods. These works resulted in the publication of The Foundations of the Arithmetic in 1884 and subsequently in 1893 and 1902, The Basic Laws of Arithmetic. However, Frege’s attempt to reduce arithmetic to logic was inadequate due to a paradox discovered by Bertrand Russell in 1902. The aim of this research was to reconstruct mathematically and logically the Russell paradox in its original formulation in the Frege’s The Basic Laws of Arithmetic. This study had as primary bibliography Frege’s works and as secondary bibliography, works of his commentators, as well as the correspondence between Frege and Russell. This research provides a logical, philosophical and mathematical formation for the educator who is in contact with this event that covers both the areas that is disciplinary today. It is a fertile moment in the history of philosophy of mathematics and logic, configured as a watershed for mathematical theories since it enabled Gödel's incompleteness theorems and non-classical logics to be formulated, and also has repercussions in contemporary philosophy and which is of unquestionable value for the teacher formation.